A COMPUTATIONAL STUDY OF THE MOLECULAR DOCKING OF BIOACTIVE COMPOUNDS FROM INDONESIAN MEDICINAL PLANTS - Windayani, Neneng; Nishida, Daiki; Cont, Sara (Research of Scientia Naturalis, 2025)
The growing interest in natural products as a source of bioactive compounds has led to the exploration of medicinal plants for their therapeutic potentials. Indonesia, with its rich biodiversity, is home to numerous medicinal plants, many of which have yet to be fully explored for their pharmacological activity. This research investigates the molecular docking of bioactive compounds derived from Indonesian medicinal plants to assess their potential interactions with various therapeutic targets. The primary objective of this study was to evaluate the binding affinities and interactions of these compounds with proteins involved in diseases such as cancer and microbial infections. Using molecular docking simulations, a range of bioactive compounds were tested for their binding potential against selected targets. The findings revealed several promising compounds with high binding affinity and stability, indicating their potential as lead candidates for drug development. This computational study highlights the significant therapeutic potential of Indonesian medicinal plants and provides a foundation for further in vitro and in vivo evaluations. The results suggest that these natural products could contribute to the development of novel pharmacological agents, particularly in the fight against cancer and infections.